Internet And Sleep Hygiene: Impact On Youth Health (Eurasian Medical Research Periodical, 2025)
This article analyzes the role of modern digital technologies, particularly the Internet, in the lifestyle of young people and its interrelation with sleep hygiene. While the educational and communicative opportunities of the Internet positively influence the intellectual development of youth, excessive and uncontrolled use may lead to sleep disturbances, as supported by scientific sources and observations. In particular, prolonged screen exposure at night can reduce melatonin secretion, disrupt the biological clock, and negatively affect cognitive and physical performance. The article also highlights the fundamental principles of sleep hygiene and their importance for youth health, psychological stability, and academic performance. Hygienic recommendations for the rational use of the Internet and maintaining proper sleep hygiene are provided. The study results demonstrate the relevance and practical significance of hygiene sciences in promoting a healthy lifestyle among young people.